Marriage and Power (Images of Authority) - Biliarsky, Ivan (Studia Ceranea, 2015)
This article is devoted to the question concerning the conceptualization of power and its religious basis in pre-modern societies, carried out through a study of the inauguration rituals – especially the marriage – that mark not only the instigation of the power of the ruler but also suggests its religious basis, conceptualization and justification. It is grounded on source material from Byzantium and its legacy in the countries of South-Eastern Europe and the Eastern Mediterranean. The analysis has shown the woman as legitimating power in the case of royalty in connection with its correspondence to marriage. The legitimation and confirmation of the kingship in some pagan cultures passed through a hierogamy, conceived as a unity with the universal harmony in the image of a chthonic goddess. From the Christian point of view the relations between the royal bride and the bridegroom was under the archetypal model of the relation of Jesus Christ to His Church. He (Christ and the christian ruler) became a priest and king of the order of Melchisedek. That is why the rite of passage to Kingship corresponds to that of marriage, instituted by Lord Jesus Christ under the model of His own relation to the Church.